Exchange Rate Management in Developing Asia: Reassessment of the Pre-crisis Soft Dollar Zone - Kenichi Ohno (Asian Development Bank Institute (ADBI), 1999)
Exchange rate rigidity is often cited as one of the primary causes of Asia's crisis. However, measured by real effective exchange rates (inflation-adjusted and tradeweighted exchange rates) using consumer prices or wholesale prices, no serious overvaluation is detected in the worst-hit economies during the pre-crisis period. Most of the Asian developing economies permitted their currencies to deviate from the strict dollar peg in the medium to long run in order to offset inflation gaps and movements of major currencies. Counterfactual simulations over the pre-crisis period show that, to stabilize competitiveness, proper adjustments for inflation by individual economies are more important than the choice of currency weights. Adoption of a common currency basket in the region does not add much stability. Pragmatic exchange rate policy rules distinguishing normal and crisis periods are suggested. To stabilize competitiveness during the normal period, no radical reform of the existing system is needed in developing Asia.
hdl:11540/4109
Keywords: 330